The Effect of the Total Physical Response (TPR) Method on Children’s Listening Skills - Tandilo Mamma, Agustinus; Sirjon (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Language development in children, especially listening, is still low. This is because in the learning process teachers still use conventional methods. In the learning process, children tend to be passive and do not respond to the information provided by the teacher. Therefore, the aim of this research is to analyze the effect of the Total Physical Response (TPR) method on the listening skills of children aged 5-6 years. This type of research is experimental research that uses a one group pretest and posttest design. The populations in the study were all early childhood children at PAUD. The sample in this study consisted of 15 children who were determined using a purposive sampling technique. The data collection method is carried out through observation using an instrument in the form of an observation sheet. The data analysis method for testing the hypothesis uses the paired sample t-test. The results of the research show that the average pretest score is 2.10, increasing in posttest data to 3.60, and the significance value is 0.000 <0.05, so it can be concluded that the Total Physical Response (TPR) method has a positive effect on the listening skills of children aged 5-6 years. The results of this research have positive implications for the field of education, especially early childhood education because the research produces findings that support previous research conducted in the Eastern region of Indonesia whose samples had different characteristics from previous research.